The Differences of Schizoid Personality Score on Medical Students of Sebelas Maret University Years 2013 with High and Low Emotional Quotient - Ivonny Rembulan Zilmi; Aris Sudiyanto; Diffah Hanim (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background : Emotional quotient is needed to control emotional changes during teenager. Teenager is also known with personality finding. Personality is a combination of emotional, attitudes, and behavior patterns of individuals. Some teenagers may have a personality disorder. Schizoid personality is one of the exsample of personality disorder. Someone with schizoid personality is tilted to be alone, over introspection, do not have best friend (only one friend) and do not want to have a relation like that and also not sensitive with rules or social habit. This research aims to see the differences of schizoid personality score on medical students of Sebelas Maret University years 2013 with emotional quotient high and low. Methods : This is an observational analytic research with case control studies approach. The research was done in Faculty of Medicine Sebelas Maret University Surakarta. Sample used are medical students years 2013 who are 18-21 years old. The sampling method used was purposive sampling after inclusive and exclusive selection based on research criteria. Dependent variable is schizoid personality, and independent variable is emotional quotient. Research subject completed (1) informed consent, (2) L-MMPI questionnaire, (3) emotional quotient questionnaire, (4) schizoid personality questionnaire. As much as 72 data were collected and analyzed using Mann Whitney. Result : There are 72 samples who 18 years old (30.6 %), 19 years old (53.8 %), 20 years old (11.1 %) and girls (68.1 %). Students with high emotional quotient have schizoid personality score lower, and vice verca. The averages of schizoid personality score on high emotional quotient is 62.19 and on low emotional quotient is 69.83 (p = 0.000). Conclusion : Statistically, there is a significant differences of schizoid personality score on medical students of Sebelas Maret University years 2013 with high and low emotional quotient. Keywords : schizoid personality, emotional quotient